Ultrasound features of the liver, spleen, kidney, and heart in dogs with canine parvoviral enteritis - Mariño, Margaret M.; Acorda, Jezie; Pajas, Arville Mar Gregorio A. (2021)
The study was performed to determine the ultrasound features of the liver, spleen, kidney, and heart in dogs positive to canine parvoviral enteritis (CPE positive). Twenty-three CPE positive puppies and 14 apparently healthy puppies (CPE negative) with an age of less than one year and a body weight of less than 10 kg were utilized in the study. Two-dimensional ultrasonography was used to identify and evaluate the hepatic, renal, splenic, and echocardiographic structures while M-mode echocardiography was used to measure dimensions of various cardiac structures and calculate cardiac indices. No significant differences were found between the measurements of the CPE positive dogs and the CPE negative dogs. The results suggest that canine parvoviral enteritis does not produce any ultrasonographically visible abnormalities in the left kidney, liver, spleen, and heart of CPE positive dogs showing clinical signs such as bloody diarrhea and vomiting. Hence, ultrasonography of the aforementioned organs is of little value in the establishment of prognosis in dogs with active canine parvoviral enteritis.
Keywords: Veterinary ultrasonography; Canine parvovirus